2022
DOI: 10.1007/s10668-022-02852-z
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity evaluation of nutrient-fortified pomegranate peel powders prepared from food waste and their feasibility as biofertilizers

Abstract: Pomegranate peel powder (PPP) is increasingly used as a bioadsorbent to decontaminate wastewaters due to its adsorptive characteristics. The application of nutrient-fortified bioadsorbents as alternatives to chemical fertilizers can provide an innovative and eco-friendly approach for sustainable waste management. Nevertheless, there is extremely limited information regarding their effects on the growth of agricultural crops. We investigated the effects of raw and nutrient-fortified PPPs on oilseed rape (Brassi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…When applied in higher concentrations, the ground materials clearly exhibit their negative allelopathic effect. This is supported by the study of Bodor et al [53], in which they demonstrated that powder made from pomegranate peel had a beneficial effect on the model plant when applied in the soil, resulting in the growth of its above-ground parts. This theory is supported by the results of Kazinczi et al [67], who investigated the allelopathy of several invasive plant species in potted experiments under greenhouse conditions and found stimulating effects in some species, which facilitated the development of cultivated plants, which indicates, on the one hand, the buffering capacity of the soil, and, on the other hand, that each species has a different allelopathic effect.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…When applied in higher concentrations, the ground materials clearly exhibit their negative allelopathic effect. This is supported by the study of Bodor et al [53], in which they demonstrated that powder made from pomegranate peel had a beneficial effect on the model plant when applied in the soil, resulting in the growth of its above-ground parts. This theory is supported by the results of Kazinczi et al [67], who investigated the allelopathy of several invasive plant species in potted experiments under greenhouse conditions and found stimulating effects in some species, which facilitated the development of cultivated plants, which indicates, on the one hand, the buffering capacity of the soil, and, on the other hand, that each species has a different allelopathic effect.…”
Section: Discussionmentioning
confidence: 63%
“…The use of soil-filled rhizotrons can be a good compromise between in vitro systems and field studies, allowing real-time, non-invasive studies of root system development [48]. Root responses of agricultural crops to different stressors have been investigated in such systems in several cases, e.g., treated with zinc [49] or nickel [50], combined heavy metal treatment modeling wastewater [51], polypropylene surgical mask fragments [52], or raw and nutrient-enriched pomegranate peel powder [53].…”
Section: Introductionmentioning
confidence: 99%